Dynamic response comparison of direct and indirect evaporation options in ORC systems for waste heat recovery - Jiménez-Arreola, Manuel (2019)
ORC is a mature technology that can be used for Waste Heat Recovery (WHR) of Internal Combustion (IC) Engines. Direct Evaporation of the organic fluid from the hot exhaust is an interesting option compared to the often preferred intermediary thermal oil loop choice due to its thermal efficiency potential and reduction of system footprint and weight. However, concerns due to dynamic variability of the hot source still hinder its consideration. In this paper, a comparison of the dynamic response of ORC evaporators with both indirect and direct evaporation is performed, under fluctuations of an IC engine exhaust according to relevant frequencies and amplitudes of a standard driving cycle. The results show the range of frequencies and amplitudes of hot source fluctuations for which direct evaporation is most feasible and the range for which special consideration must be taken.